2022
DOI: 10.3389/fendo.2022.1079541
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic investigations of diabetic ocular surface diseases

Abstract: With the global prevalence of diabetes mellitus over recent decades, more patients suffered from various diabetic complications, including diabetic ocular surface diseases that may seriously affect the quality of life and even vision sight. The major diabetic ocular surface diseases include diabetic keratopathy and dry eye. Diabetic keratopathy is characterized with the delayed corneal epithelial wound healing, reduced corneal nerve density, decreased corneal sensation and feeling of burning or dryness. Diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 310 publications
1
26
0
1
Order By: Relevance
“…Corneal sections of diabetic rats in previous studies 44 , 56 showed severe degenerative changes, such as edema, degradation of its collagen fibers, and corneal neovascularization, which are consistent with the findings of this study. Severe vascularization of acellular bowmans membrane, corneal edema and cornea fibrosis as obtained in the histology of the cornea of the diabetic group suggests that they were at risk of developing diabetic corneal complications.…”
Section: Discussionsupporting
confidence: 92%
“…Corneal sections of diabetic rats in previous studies 44 , 56 showed severe degenerative changes, such as edema, degradation of its collagen fibers, and corneal neovascularization, which are consistent with the findings of this study. Severe vascularization of acellular bowmans membrane, corneal edema and cornea fibrosis as obtained in the histology of the cornea of the diabetic group suggests that they were at risk of developing diabetic corneal complications.…”
Section: Discussionsupporting
confidence: 92%
“… 57 The cornea is the most densely innervated tissue of the body; after corneal injury, the regeneration of the local sensory nerves is regulated by numerous complex molecules. 19 , 20 Different AGMs have distinct effects on corneal nerve growth. For example, during early development, both Sema3A and SLIT2 are involved in preventing nerves from entering the corneal stroma.…”
Section: Discussionmentioning
confidence: 99%
“…According to the International Diabetes Federation’s survey, the worldwide population of individuals with diabetes is predicted to reach 650 million by 2040 . DM occurs because of insufficient insulin secretion or insulin resistance, which leads to the accumulation of glucose in the circulation. , When the blood glucose level exceeds the normal range (≥11.1 mmol/L), it causes hyperglycemia, and prolonged hyperglycemia can cause cardiovascular disease, ketoacidosis, stroke, renal failure, neuropathy, lower limb amputation, and retinopathy. Hence, continuous control of the glucose level is key to treating patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%